TESTOSTERONE AND SOCIAL ISOLATION INFLUENCE ADULT NEUROGENESIS IN THE DENTATE GYRUS OF MALE RATS - Spritzer, Mark D. (2011)
Testosterone has been previously shown to enhance adult neurogenesis within the dentate gyrus of adult male rats, whereas social isolation has been shown to cause a decrease in adult neurogenesis under some conditions. The current study tested the combined effects of testosterone and social isolation upon adult neurogenesis using two experiments involving adult male rats. For both experiments, half of the subjects were pair-housed and half were housed individually for the duration of the experiments (34 days). For experiment 1, the subjects were divided into four groups (n=8/group): 1) sham/pair-housed, 2) sham/isolated, 3) castrate/pair-housed, and 4) castrate/isolated. Rats in the castrate groups were bilaterally castrated, and rats in the sham groups were sham castrated. For experiment 2, all rats were castrated and the effects of testosterone were tested using daily injections of testosterone propionate (0.500 mg/rat for 15 days) or the oil vehicle. Subjects were divided into four groups (n =8/group): 1) oil/pair-housed, 2) oil/isolated, 3) testosterone/pair-housed, and 4) testosterone/isolated. All rats were injected with 5-Bromo-2’-deoxyuridine (BrdU, 200 mg/kg body mass) and immunohistochemistry was used to determine levels of neurogenesis following a 16-day cell survival period. For experiment 1, castrated subjects had significantly fewer BrdU-labeled cells along the granule cell layer and sub-granular zone (GCL+SGZ) of the dentate gyrus than did intact subjects, and this effect was mainly due to low levels of neurogenesis in the castrate/isolated group. For experiment 2, social isolation caused a significant decrease in neurogenesis within the GCL+SGZ relative to the pair-housed groups. Testosterone injections did not buffer against this effect but instead tended to cause a decrease in neurogenesis. Thus, social isolation reduced hippocampal neurogenesis, but the effects of testosterone were inconsistent. This suggests that normal circulating levels of testosterone may buffer against the neurogenesis-impairing effects of isolation, whereas high doses of testosterone do not.